1997
DOI: 10.1037/1040-3590.9.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for the MMPI-2 in child custody litigation.

Abstract: Minnesota Multiphasic Personality Inventory-2 (MMPI-2) norms based on 508 child custody litigants are presented. Defensive underreporting and self-favorability were often exhibited along with an elevation on the Over-Controlled Hostility (O-H) scale. Highest mean clinical scale scores were Hysteria, Paranoia, and Psychopathic Deviate. Differences were not found among mothers, fathers, and stepparents, indicating that a single set of norms is suitable. Findings highlight the importance of context specificity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
81
2
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 38 publications
12
81
2
1
Order By: Relevance
“…Further, this positive self-presentation has a significant suppressive effect on the clinical scale scores. These findings closely replicate our earlier (unpublished) results from a previous cohort of 76 examinees (Moretti, Carr, & Cue, 2002) and extend similar re- Siegel (1996), Bathurst et al (1997), Posthuma and Harper (1998), and Bagby et al (1999) have found mean L scale scores to be somewhat elevated (t scores of 58, 56, 53, and 52.3, respectively), with elevations on K slightly higher than L in each study (t scores of 60, 58.7, 56, and 57.5, respectively). In contrast, our findings show dominant L scale elevations.…”
Section: Minnesota Multiphasic Personality Inventory (2nd Ed)supporting
confidence: 82%
See 1 more Smart Citation
“…Further, this positive self-presentation has a significant suppressive effect on the clinical scale scores. These findings closely replicate our earlier (unpublished) results from a previous cohort of 76 examinees (Moretti, Carr, & Cue, 2002) and extend similar re- Siegel (1996), Bathurst et al (1997), Posthuma and Harper (1998), and Bagby et al (1999) have found mean L scale scores to be somewhat elevated (t scores of 58, 56, 53, and 52.3, respectively), with elevations on K slightly higher than L in each study (t scores of 60, 58.7, 56, and 57.5, respectively). In contrast, our findings show dominant L scale elevations.…”
Section: Minnesota Multiphasic Personality Inventory (2nd Ed)supporting
confidence: 82%
“…In contrast, in the postdivorce custody literature, there have been reviews of test utilization, presentations of normative data, and examinations of positive self-presentation by parents. It is noteworthy that the reviews of test utilization have consistently indicated that the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) is the most commonly used instrument (e.g., Ackerman & Ackerman, 1997;Hagen & Castagna, 2001;Keilin & Bloom, 1986;Quinnell & Bow, 2001), that normative data on the MMPI-2 have been presented (Bagby, Nicholson, Buis, Radovanovic, & Fidler, 1999;Bathurst, Gottfried, & Gottfreid, 1997;Ollendick & Otto, 1984), and that the issue of defensive responding has been specifically addressed (Bagby et al, 1999;Bathurst et al, 1997;Medoff, 1999;Posthuma & Harper, 1998;Siegel, 1996). These authors have generally reported that MMPI-2 measures of positive selfpresentation tend to be slightly or moderately elevated in this population, although the clinical significance of the elevations has been questioned (Medoff, 1999).…”
mentioning
confidence: 99%
“…Heilbrun (1995) noted the need to assess the individual's response style in making interpretation of assessment information in child-custody cases, and studies have found that parents in custody litigation typically score .5 to 1 standard deviation above the mean on MMPI-2 L and K scales in efforts to present themselves well (Bathurst, Gottfried, & Gottfried, 1997;Miller, Lape-Brinkman, Roche, Cox, & Motheral, 1999). Favorable self-presentation can take many forms, running a gamut from outright lying to "putting one's best foot forward," from being ingratiating with the examiner to simply showing polite manners.…”
mentioning
confidence: 97%
“…The majority of studies have focussed on child custody evaluations with normative MMPI-2 data being published for this population group (Archer, Hagan, Mason, Handel, & Archer, 2012;Bagby, Nickolson, Buis, Radovanovic, & Fidler, 1999;Bathurst, Gottfried, & Gottfried, 1997;Siegel, 1996). Findings from these studies have indicated that those undergoing child custody evaluations generally exhibit defensive responding and heightened efforts at social desirability.…”
mentioning
confidence: 98%